DISCLOSURE OF ISLAMIC SOCIAL REPORTING A COMPARATIVE STUDY OF INDONESIA AND MALAYSIA - Nugraha, Erik; Noviantini, Tri Anita; Setiawan, Audita (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
This study aims to describe and determine the differences in the disclosure of Islamic Social Reporting (ISR) in Islamic Banks in Indonesia and Malaysia. Islamic Social Reporting (ISR) is an extension of the reporting standards of social performance as a reflection of the company's role in a spiritual perspective. The method used in the research is descriptive comparative method using cross-sectional data types. The population in this study is Islamic Banks in Indonesia, which are as many as 13 banks and in Malaysia which are as many as 15 banks, the sampling technique used in this study uses census sampling techniques. The data analysis technique used is the Independent t-test. Based on the results of the study there are not differences in the disclosure of Islamic Social Reporting (ISR) in Islamic Banks in Indonesia and Malaysia, but the level of disclosure of Islamic Social Reporting (ISR) in Islamic Banks in Malaysia is better than Islamic Banks in Indonesia.Â